Pendidikan Kesehatan (Buku KIA 2020) Khusus Ibu di Masa Pandemi Covid-19 di PMB Bumi Cinta Gorontalo - Rauf, Efri Leny; Katili, Dwi Nur Octaviani; Umar, Siskawati (Idea Pengabdian Masyarakat, 2021)
Knowledge of mothers about the use of Maternal and Child Health (MCH) books, which is still considered only as a health record book for health workers, is an obstacle in shaping the health behavior of pregnant women about the importance of routine pregnancy check-ups, understanding the danger signs of early pregnancy, the importance of taking Fe tablets regularly, as well as daily health care. According to the initial survey of the service team, we see that knowledge and understanding have an impact on the awareness of pregnant women about the contents of the MCH book, especially now that the MCH book has been revised so that the importance of health education on MCH books needs to be explained again in the independent practice of the midwife of the love of Gorontalo. The method of service is through lectures/counseling, discussion and question and answer. As a result of our dedication, we get the enthusiasm of pregnant women in listening to our explanations and asking important things they want to know